Acupuncture for whiplash-associated disorder following road traffic collision: a physiotherapy service evaluation. Issue 4 (August 2020) - Stuart, Samuel; Armstrong, Michael; Sewell, Jennifer; Dixon, Cheryl; Morris, Rosie
Background: Whiplash-associated disorder (WAD) is a common musculoskeletal condition that frequently occurs following a road traffic collision. Physiotherapy is often prescribed to help with the symptoms and injuries. Research evidence has demonstrated that acupuncture may be beneficial, but no studies have examined the routine clinical use of acupuncture by physiotherapists for treatment of WAD. Therefore, a physiotherapy service evaluation was conducted to examine the effects of acupuncture on WAD following a road traffic collision. Methods: This study involved 87 patients who attended a private physiotherapy practice following a road traffic collision after referral by their solicitor as part of a personal injury claim. Patients were included if they had been diagnosed with WAD (grades I–III) and received acupuncture as part of their treatment. An average of three sessions of acupuncture were received, which primarily involved needling of traditional acupuncture points and/or myofascial trigger points of the neck and upper/lower back. Results: Pain significantly reduced ( p  < 0.001). Musculoskeletal outcome measures including neck disability index, Oswestry low back pain scale and Quick disabilities of the arm, shoulder and hand (Quick-DASH) scale also significantly improved (all p  < 0.001). Adverse events were minor. The majority of the patients (n = 66) were able to return to full-work duties following treatment. Conclusion: Acupuncture appears to be an effective clinical treatment for WAD following a road traffic collision and should be considered by physiotherapists working with such patient groups.